Study of trapping centers in undoped Al₂O₃ crystals using thermoluminescence methods - Gumenjuk, A.F.; Kutovyi, S.Yu.; Grebenovych, M.O. (Functional Materials, 2005)
The energy spectra of trapping centers (TC) in specially undoped α-AI₂O₃ crystals within temperature range of 80 to 500 К have been studied using thermoluminescence (TL). In this work, the oscillation regularity revealed before in the TC energy spectrum has been studied in more detail as well as the decay features of some anomalously broad TL peaks. The values of the TC thermal activation energy form the single oscillation series

En = πωtl(n +1/2), πωtl = 64 2 cm⁻¹ (0.079 eV). The corresponding Raman line 645 ciri1 is the highest frequency of the full-symmetric Ag modes. This regularity is concluded to be due to the polaron nature of the traps. A method has been proposed to establish the cause of TL peak broadening, i.e., to determine its structure. The TL peak at 280 К has been shown to have a complex structure being a superposition of at least two elementary peaks close to one another. The intensity of the complex peak low-temperature component increases faster than that of the high-temperature one as the light sum rises. Методами термолюминесценции (ТЛ) исследован энергетический спектр ловушек в специально не легированных кристаллах α-Аl₂О₃, в интервале температур 80-500 К. В данной работе подробнее исследована найденная ранее осцилляторная закономерность в энергетическом спектре ловушек, а также особенности высвечивания некоторых аномально широких пиков ТЛ. Обнаружено, что энергии активации ловушек формируют

одну осцилляторную серию: En = πωтл(n +1/2), πωтл = 64 2 cm⁻¹ (0.079 эВ). В спектре комбинационного рассеяния соответствующая линия 645 ем 4 отвечает наиболее высокочастотному из полносимметричных Ag колебаний. Сделан вывод, что эта закономерность обусловлена поляронной природой ловушек. Предложена методика, позволяющая установить причину расширения пика ТЛ, то есть определить его структуру. Показано, что пик ТСЛ при 280 К сложный и является суперпозицией, по крайней мере, двух близко расположенных элементарных пиков, причем интенсивность низкотемпературной компоненты сложного пика с увеличением светосуммы возрастает быстрее, чем высокотемпературной. Методами термолюмінесценції (ТЛ) досліджено енергетичний спектр центрів прилипання у спеціально не легованих кристалах α-Аl₂О₃, в інтервалі температур 80-500 К. В даній роботі детальніше досліджено знайдену раніше осциляторну закономірність в енергетичному спектрі пасток, а також особливості висвічування деяких аномально широких піків ТЛ. Виявлено, що енергії термічної активації ЦП утворюють одну осциляторну серію: En = hωtl(n +1/2), hωtl = 0.079 eB (642 см⁻¹ ). У спектрі комбінаційного розсіяння відповідна лінія 645 см⁻¹ є найбільш високочастотним з повноси-метричних (Ag) коливань. Зроблено висновок, що закономірність зумовлена полярон-ною природою пасток. Запропоновано методику, яка дозволяє встановити причину розширення піка ТЛ, тобто визначити його структуру. Показано, що пік ТСЛ при 280 К має складну структуру і є суперпозиціє, принаймні двох близько розміщених елементарних піків, причому інтенсивність низькотемпературної компоненти складного піка із збільшенням світлосуми зростає швидше, ніж високотемпературної.